Optimising dynamic mechanical analysis experiments on soft rubbers for use in time temperature superposition - Akash R. Trivedi; Nicholas Hawkins; Clive R. Siviour (MethodsX, 2022)
Rubbers are ubiquitous in engineering applications where they are often subjected to loading leading to high strain rate deformation. The strong rate and temperature dependence of rubbers and their composites motivates research into understanding their mechanical response under a wide range of conditions. However, experimental characterisation of the rate-temperature dependence of soft rubbers is challenging. In this methods paper, an improved methodology is proposed for conducting Dynamic Mechanical Analysis (DMA) experiments on rubbers. The higher quality data produced can be used in time-temperature superposition (TTS) applications to derive a more accurate definition of the rubber’s rate-temperature dependence. Overall, the improvements obtained can be summarised as follows: • Reducing clamping artefacts due to volume expansion • Ensuring high quality temperature stability • Improving the contact area between the specimen and the clamps